Interactivity as a Determinant of University Library Websites Credibility in Universities In Kwara State, Nigeria - Mahammuod, Sulyman Olaitan; Abdulahi Olayinka , Isiaka; Agboola Shuaib , Olarongbe; Qudus Ajibola , Bankole (International Journal of Knowledge Content Development & Technology, 2025)
The rapid advancement in Web technology has shifted the role of organizational websites from mere communication tools to strategic tools for gaining a competitive advantage. The concept of interactivity is highly associated with modern communication technologies, especially the internet and the Www, which deal with enhancing the accessibility of information to users. this study aim at determining interactivity as a determinant of university library websites credibility in universities in Kwara State and examine several factors like interactivity, credibility, library website, university library website. This is a descriptive survey of correlational type. The population comprised all registered students of the institutions understudied which were selected purposively. Simple random sampling was used in the selection of respondents for this study. The instrument used for data collection was a questionnaire. Data collected were analyzed using frequency count and percentages. The result shows that 67% of respondents agreed that the university library website facilitates two-way communication, navigation buttons were on every pages of library website, completeness and unambiguity makes university library website more credible. The study concluded that interactivity influences university library website credibility in universities in Kwara State, Nigeria.